Association of Proliferative Diabetic Retinopathy in the Elderly with the Blood Complement System - O. L. Fabrikantov; N. M. Agarkov; I. V. Lev; T. S. Gurko; S. I. Nikolashin (Oftalʹmologiâ)
A common complication of diabetes mellitus, mainly type 2, is diabetic retinopathy, among which the most unfavorable form for complete loss of vision is considered to be proliferative diabetic retinopathy. The participation of the complement system in the development of proliferative diabetic retinopathy is mainly devoted to experimental work on a limited number of blood complement components and without assessing their risk in the pathogenesis of the disease. The purpose of the study was to determine the association of components of the blood serum complement system with the development of proliferative diabetic retinopathy in the elderly. In clinical conditions, 115 patients 60–74 years old suffering from proliferative diabetic retinopathy and 48 patients of the same age with the absence of this ophthalmopathology were examined. The components of the blood complement system were studied by enzyme immunoassay and hemolytic method. The relative risk of the influence of the complement components was calculated according to the generally accepted method. There was a statistically significant increase in the blood serum of patients with proliferative diabetic retinopathy of most components of the complement system, with the exception of the C1 ing. and C5 components. The content of the C3a component increased especially to 127.6 ± 4.7 ng / ml versus 30.4 ± 3.5 ng/ml in the control, the C5a component to 5.6 ± 0.5 ng/ml versus 2.4 ± 0.3 ng/ml, and factor H to 228.7 ± 4.9 versus 106.3 ± 3.8 mng / ml, respectively. The highest value of the relative risk among the studied components is inherent in the C3a component of the blood complement with a reliable confidence interval of 4,451–5,103. The development of proliferative diabetic retinopathy in the elderly is associated with an increased content of C3a, C5a components and factor H in the blood serum, which can be used to develop targeted therapy for this disease.